Governance and the Role of Legal Aspects in the Fuel Pricing in Indonesia - Sihombing, B.F.; Lisdiyono, Edy (International Journal of Energy Economics and Policy, 2018)
This research aims to analyze about the governance policy and the role of legal politic aspects in the unification of fuel prices in Indonesia. This study used the mixed method, which is the analysis of data of fuel, and the normative juridical methods, investigating legal principles contained in the rules and legislation in determining the fuel prices. Although the nature of this research is descriptive analytical, the study was intended to provide the accurate data as much as possible about the condition of fuel pricing by describing the facts using avalaible data. The results of the discussion concluded that the legal and politic aspects have noticeable role in the determination of unification of fuel prices and in ensuring fuel availability thorough Indonesia, as well as the supply of fuel to the public in the domestic market. The study results are regarded important to provide another perspective in analyzing the role of legal politic elements in fuel pricing, that not merely focus on economic and quantitave analysis. The results show that the fuel pricing can be used as the basis for bargaining power, and political interests, making it is frequently not easy to unify the price nationally. The study also gives some legal justifications and social foundations of administered price of fuel that can be conducted by developing countries, especially Indonesia, having national oil companies and the state body on oil and gas management. Keywords: Administered Price, Fuel Supply, Legal Justification, State Role JEL Classifications: K23, K32, Q48